Mandarin Tone Identification by Tone-Naïve Musicians and Non-musicians in Auditory-Visual and Auditory-Only Conditions - Han, Yueqiao; Goudbeek, Martijn; Mos, Maria; Swerts, Marc (Frontiers in Communication, 2019)
A considerable number of studies have shown that musical ability has a positive effect on language processing. Extending this body of work, this study investigates the effects of musicality and modality on Mandarin tone identification in tone-naïve participants. To examine the effects of visual information in speech, Mandarin tones were presented in auditory-only or auditory-visual modalities to participants with or without musical experience. The Goldsmith Musicality Index was used to assess the musical aptitude of the participants. Overall, musicians outperformed non-musicians in the tone identification task in both auditory-visual and auditory-only conditions. Both groups identified tones more accurately in the auditory-visual condition than in the auditory-only condition. In addition, performance differed by tone: musicality holds its main effect on each level of tone; while the influence of modality differs for individual tones; the identification of tone 3 (a low-falling-rising) proved to be the easiest, while tone 4 (a high-falling tone) was the most difficult to identify for all participants. Out of all the musical skills measured by the Goldsmith Musicality Index, the amount of musical training was the only predictor that had an impact on the accuracy of Mandarin tone perception. These findings suggest that learning to perceive Mandarin tones benefits from musical expertise, and visual information can facilitate Mandarin tone identification, but mainly for tone-naïve non-musicians.